4c+3-c=-7+2+c

Simple and best practice solution for 4c+3-c=-7+2+c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4c+3-c=-7+2+c equation:


Simplifying
4c + 3 + -1c = -7 + 2 + c

Reorder the terms:
3 + 4c + -1c = -7 + 2 + c

Combine like terms: 4c + -1c = 3c
3 + 3c = -7 + 2 + c

Combine like terms: -7 + 2 = -5
3 + 3c = -5 + c

Solving
3 + 3c = -5 + c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
3 + 3c + -1c = -5 + c + -1c

Combine like terms: 3c + -1c = 2c
3 + 2c = -5 + c + -1c

Combine like terms: c + -1c = 0
3 + 2c = -5 + 0
3 + 2c = -5

Add '-3' to each side of the equation.
3 + -3 + 2c = -5 + -3

Combine like terms: 3 + -3 = 0
0 + 2c = -5 + -3
2c = -5 + -3

Combine like terms: -5 + -3 = -8
2c = -8

Divide each side by '2'.
c = -4

Simplifying
c = -4

See similar equations:

| 5b-10=7b+12 | | V^2-14=5b | | 5y-x+6=0 | | -8+9b=2+14b | | 5p+2=2p+14 | | 5(c-7)-2(3x-4)=3x | | 2r^2=20r-42 | | 16x+8+10x-10=180 | | 15x+3=-14x+5 | | 3x+6+5x=46 | | 7+3a=-1-5a | | X+5=x-7 | | 14x+6=42 | | -3000x^2+7500=0 | | -2y+5(y-7)=-17 | | X-3i= | | -5m-2=8 | | 10x+15+3x+35=180 | | x-4=12+5x | | 12=9+3x | | X-(6)=-23 | | 96x-1+85x=180 | | 184=3(-7a+8)+a | | 9+-0= | | 106x-1+77x-2=180 | | -62=8(6v+2)-6(v-1) | | 7(u+2)-5u=-2 | | 5(-3)-(-6)= | | 21(x+1)-14(x-1)=21x | | 3(x-24)+3(x-2)=18 | | 2n-6=9+5n | | 10x-10+16x+8=180 |

Equations solver categories